Atraumatic restorative treatments improve child oral health‐related quality of life: A noninferiority randomized controlled trial. Issue 4 (18th May 2020) - Arrow, Peter; Forrest, Helen
Abstract: Objectives: Management of dental caries under dental general anaesthesia (DGA) in young children improves their quality of life. A randomized controlled trial was undertaken to test the changes in oral health‐related quality of life among children treated under a DGA or managed using the Atraumatic Restorative Treatment and Hall crown approaches (ARTs). Methods: Children scheduled for a DGA for the management of dental caries after assessment at the Oral Health Centre of Western Australia were invited to participate. Inclusion and exclusion criteria were applied. Child oral health‐related quality of life (COHRQoL) was evaluated through the Early Childhood Oral Health Impact Scale (ECOHIS) and the child‐specific Caries Impacts and Experiences Questionnaire for Children (CARIES‐QC) at baseline and 12 months after consent. The changes in child oral health‐related quality of life were analysed on an intention‐to‐treat basis. Paired t ‐test and Wilcoxon's matched‐pairs rank test were used for within‐group comparison and t ‐test, Mann‐Whitney test, and test of proportions for between‐group comparisons. Linear regression was used for multivariable analyses of the follow‐up scores. Results: Sixty‐five parents/carers agreed to participate and were randomized (Test = 32; Control = 33). Mean age = 4.7 years, SD 1.1; 51% male. At baseline, there were no statistically significant differences in age and sex between the groups; however, the ARTs group reported higher ECOHIS scores. At follow‐up, both the ARTs and DGA groups had lower ECOHIS scores (20.7 vs 12.9 and 14.4 vs 13.3, respectively) and CARIES‐QC scores (12.6 vs 7.1 and 9.9 vs 8.4, respectively). The within‐group differences in the ARTs group were statistically significant while the differences in the DGA group were not, P  < .01 and P  > .05, respectively. In a linear regression of the follow‐up scores, being in the DGA group increased the follow‐up scores, but it was no longer statistically significant while baseline impact scores were significantly associated with greater follow‐up scores for both the ECOHIS and the CARIES‐QC, P  < .01. Conclusion: The child oral health‐related quality life among children scheduled for dental general anaesthesia improved after receiving minimally invasive, atraumatic restorative treatments of dental caries.